2011
DOI: 10.1093/ecam/nep148
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Arthritic Activity of Bartogenic Acid Isolated from Fruits of Barringtonia racemosa Roxb. (Lecythidaceae)

Abstract: The fruits of Barringtonia racemosa are prescribed in the ayurvedic literature for the treatment of pain, inflammation and rheumatic conditions. In present investigation, activity guided isolation of bartogenic acid (BA) and its evaluation in the Complete Freund's Adjuvant (CFA)-induced arthritis in rats is reported. Among the various extracts and fractions investigated preliminarily for carrageenan-induced acute inflammation in rats, the ethyl acetate fraction displayed potent anti-inflammatory activity. Lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 33 publications
1
65
0
2
Order By: Relevance
“…Hematological parameters like red blood cell (RBC) count, white blood cell (WBC) count, hemoglobin (Hb) value, erythrocyte sedimentation rate (ESR) were evaluated using routine laboratory methods (Patil, Patil, Jadhav, 2009). The separated serum was analyzed for urea, uric acid and serum biomarkers viz.…”
Section: Hematological Parametersmentioning
confidence: 99%
“…Hematological parameters like red blood cell (RBC) count, white blood cell (WBC) count, hemoglobin (Hb) value, erythrocyte sedimentation rate (ESR) were evaluated using routine laboratory methods (Patil, Patil, Jadhav, 2009). The separated serum was analyzed for urea, uric acid and serum biomarkers viz.…”
Section: Hematological Parametersmentioning
confidence: 99%
“…It had been previously reported that moderate increase in WBC count occurs in arthritis due to an IL-1B mediated rise in the respective ColonyStimulating Factors (Patil et al, 2009). Similarly, an increase in the ESR is attributed to the accelerated formation of endogenous proteins such as fibrinogen and a/b globulin, and such a rise in the ESR indicates an active but obscure disease process (Sarika et al, 2010).…”
Section: Resultsmentioning
confidence: 95%
“…In 2008, NurulMaryam et al, 60 reported that great amount of β-carotene and lycopene were found in the ethanolic extract of B. racemosa leaf. Later on, further studies had been published which verified the presence of bartogenic acid done by Patil et al 61 . In such discovery, they confirmed the isolation of bartogenic acid from the fruits of this plant species.…”
Section: Terpenoidsmentioning
confidence: 85%